2020
DOI: 10.1080/13697137.2020.1806816
|View full text |Cite
|
Sign up to set email alerts
|

Uterine bleeding with hormone therapies in menopausal women: a systematic review

Abstract: Uterine bleeding is a common reason why women discontinue menopausal hormone therapy (HT). This systematic review compared bleeding profiles reported in studies for continuous-combined HT approved in North America and Europe for moderate to severe vasomotor symptoms in postmenopausal women with a uterus. Non-head-to-head studies showed that uterine bleeding varies by formulation and administration route, with oral having a better bleeding profile than transdermal formulations. Cumulative amenorrhea over a year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…After the menopause, the endometrium normally undergoes a gradual atrophy, starting with an inactive phase in which neither proliferation nor secretion is present and ending in a thin layer, often with cystic cavities (30). HRT, most commonly a combination of estrogen and progestogen, may interfere with the physiological atrophy (30,31), and vaginal bleeding is a common side effect (32). Ljung et al (12) observed a slightly stronger association between vaccination and PMB after the third dose in a subsample analysis of nonhormone users as compared to the analysis on the complete sample.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After the menopause, the endometrium normally undergoes a gradual atrophy, starting with an inactive phase in which neither proliferation nor secretion is present and ending in a thin layer, often with cystic cavities (30). HRT, most commonly a combination of estrogen and progestogen, may interfere with the physiological atrophy (30,31), and vaginal bleeding is a common side effect (32). Ljung et al (12) observed a slightly stronger association between vaccination and PMB after the third dose in a subsample analysis of nonhormone users as compared to the analysis on the complete sample.…”
Section: Discussionmentioning
confidence: 99%
“…After the menopause, the endometrium normally undergoes a gradual atrophy, starting with an inactive phase in which neither proliferation nor secretion is present and ending in a thin layer, often with cystic cavities ( 30 ). HRT, most commonly a combination of estrogen and progestogen, may interfere with the physiological atrophy ( 30 , 31 ), and vaginal bleeding is a common side effect ( 32 ). Ljung et al.…”
Section: Discussionmentioning
confidence: 99%
“…Cumulative amenorrhoea over 12 months was lower in the transdermal preparations (9-27%), when compared to oral preparations (18-61%), irrespective of the constituents. 93 As perimenopausal women have higher rates of unscheduled bleeding and proliferation on biopsy, than postmenopausal women, 94,95 an oral preparation (if no risk factors for thrombosis), could be offered as either, a first-line therapy or, to women whose initial preference was for transdermal but have unscheduled bleeding episodes despite adjustments.…”
Section: Recommendations For Management According To Endometrial Hist...mentioning
confidence: 99%
“…Consideration should also be given to assessment of the endometrial cavity by hysteroscopy where clinically indicated or in cases with persistent bleeding and an endometrial biopsy obtained to assess for and exclude endometrial pathology. 2,[30][31][32] The risk of endometrial cancer in women with unscheduled bleeding on HRT is significantly lower than that with postmenopausal bleeding in women not on HRT especially in women who had not been experiencing bleeding before commencing HRT. 4 For the majority of women with unscheduled bleeding on HRT, modifying progestogen intake often controls the bleeding especially in women who experience unscheduled bleeding in the first few months after commencing HRT.…”
Section: Unscheduled Bleeding On Hrtmentioning
confidence: 99%
“…Consideration should also be given to assessment of the endometrial cavity by hysteroscopy where clinically indicated or in cases with persistent bleeding and an endometrial biopsy obtained to assess for and exclude endometrial pathology. 2,3032…”
Section: Unscheduled Bleeding On Hrtmentioning
confidence: 99%